The Impact of Sustainable Innovation, Entrepreneurship Training and Digital Engagement on the Business Performance: A Quantitative Analysis - Mary Priteena, S. (Shanlax International Journal of Management, 2025)
Purpose: This study investigates the influence of sustainable innovation, entrepreneurship training, and digital engagement on business performance using empirical data.Methodology: A quantitative methodology was employed using data collected from 30 companies selected through purposive sampling. Descriptive and inferential statistics, including multiple regression, ANOVA, and t-tests, were conducted using SPSS 23 and Excel.Findings: Results revealed that entrepreneurship training (t=2.142, p=0.041) and digital engagement (t=2.421, p=0.022) significantly influence profit growth. The regression model explains 32.2% (R²=0.322) of the variance in business performance. Additionally, ANOVA results show that IT integration and sustainable innovation scores significantly vary across compliance levels (F=2.857, p=0.044). Government support was found to significantly impact profit growth (t=-6.569, p<0.001).Research Implications: The study emphasizes integrating entrepreneurship development and digital strategies into sustainability-oriented business models for better performance.Practical Implications: The findings highlight the need for optimizing government support programs and promoting digital platforms and training to enhance business sustainability.Originality/Value: The originality lies in the integrated analysis of innovation, training, and digital engagement offering a holistic perspective on their synergistic effects on business outcomes.